Investigation of the shelf life of banana ‘MAS’ (Musa acuminata Colla) using gamma irradiation - Nur Farhatul Huda Sopi; Mohd Zulfadli Adenan (Penerbit Universiti Kebangsaan Malaysia, 2021)
To investigate the shelf life of banana ‘Mas’ (Musa acuminata Colla) using gamma rays in Malaysia. An experimental study to investigate the shelf life of banana Mas using different doses of gamma radiation. Different doses will be given to each group of banana Mas which are 0 (untreated control), 0.4, 0.8 and 1.2 kGy. The irradiated groups were being irradiated by gamma radiation at the National University of Malaysia (UKM) using Gamma Cell 220 Excel Cobalt-60 source. The observation was performed on the physical changes of the sample such as peel colour, decay rate, and physiological weight loss. Findings have shown that the high dose of gamma radiation caused the darkening of the peel and accelerate the ripening process depend on the varieties of the bananas. Among all, group B (0.4 kGy) has the lowest PWL (Physiological Weight Loss) and decay rate when compared to the other groups. The result of the one-way ANOVA test on the weight loss was not statistically significant. The dose of 0.4 kGy was the most effective one in delaying the ripening process for banana Mas when compared to the other group samples.